2013
DOI: 10.18697/ajfand.56.11945
|View full text |Cite
|
Sign up to set email alerts
|

Fatty and amino acids composition of selected wild edible mushrooms of Bunyoro sub-region, Uganda

Abstract: For thousands of years, mushrooms have long been used for their health promoting properties. The aim of this study was to determine the fatty acids and amino acids contents in priority wild mushrooms: Termitomyces microcarpus, Termitomyces sp. (Bunyanaka), Termitomyces globulus, Termitomyces eurrhizus and Polyporus tenuiculus widely consumed in Bunyoro Sub-region, Uganda. The study revealed seventeen amino acids using pre-column derivatization with a phenylisothiocyanate followed by HPLC-UV-vis, and tryptophan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Total of amino acids of T. albuminosus's mycelia was 50.37 ± 0.26 mg/g (about 5.0% of dry weight) (Tsai et al, 2006), which was much lower than the result of this study. Amino acid contents of T. eurrhizus and T. microcarpus were 23.6% and 59.0% of their dried fruit bodies, respectively (Nakalembe & Kabasa, 2013). High protein as well as amino acids contents in this study indicated that cultured media and fermentation process were suitable for T. clypeatus.…”
Section: Chemical Components Of T Clypeatus's Mycelia Cultured In the Stirred-tank Bioreactormentioning
confidence: 57%
“…Total of amino acids of T. albuminosus's mycelia was 50.37 ± 0.26 mg/g (about 5.0% of dry weight) (Tsai et al, 2006), which was much lower than the result of this study. Amino acid contents of T. eurrhizus and T. microcarpus were 23.6% and 59.0% of their dried fruit bodies, respectively (Nakalembe & Kabasa, 2013). High protein as well as amino acids contents in this study indicated that cultured media and fermentation process were suitable for T. clypeatus.…”
Section: Chemical Components Of T Clypeatus's Mycelia Cultured In the Stirred-tank Bioreactormentioning
confidence: 57%
“…C. fracidus has the highest amount (26.34 ± 2.36 GlyE/g extract) of amino acids contents. Globally, the Termitomyces had high content of amino acid compared to that of T. reticulatus obtained by Njouonkou A-L, et al [13] but lower than in T. eurrhizus, T. globulus and T. microcarpus [30,32]. The total amino acids contents of mushrooms species may be ranked as follow: C. fracidus> T. umkowaani>T Thiols include many organic compounds that contain a sulphydryl group (-SH) [33].…”
Section: Discussionmentioning
confidence: 96%
“…Nervonic acid is the second most abundant (0.94%) monounsaturated fatty acid presently recorded in L. sajor-caju. This is an important monounsaturated fatty acid reported to be involved in the biosynthesis of nerve cell myelin and preventing disorders such as adrenoleukodystrophy and multiple sclerosis in elderly people (Sargent et al, 1994;Nakalembe, Kabasa, 2013).…”
Section: Discussionmentioning
confidence: 99%